PENOSCROTAL PAGET’S DISEASE – CASE REPORT AND LITERATURE REVIEW - Pejnović, Luka; Đurišić, Igor; Živković, Ognjen; Petrović, Ognjen; Petrović, Ivana; Inić, Zorka; Marković, Ivan (Srpski medicinski časopis Lekarske komore, 2024)
Introduction: Penoscrotal Paget’s disease is very rare worldwide, with a small number of case reports, and it thus represents a major dilemma in diagnosis and treatment. Case report: An 81-year-old man presents himself to the Institute of Oncology and Radiology of Serbia (IORS) for the first time due to an ulcerated and erythematous tumor change about 10 cm in diameter covered with squamous plates, which extends from the groin region on the left to the scrotum. The tumefaction is erythematous, bloody and it occasionally bleeds, and the patient complains of occasional pain in the left leg. Previously, a biopsy of the mentioned tumor change was performed in another institution, and the PH finding was in favor of extramammary Paget’s disease. The patient was presented to the IORS council, which decided on operative treatment. Conclusion: This rare disease is also found outside of clinically visible lesions, positive resection margins are common, and this represents the main risk factor for disease recurrence. Accurate preoperative diagnosis and proper surgical treatment are crucial for preventing relapses and repeat operations, making them key factors in improving survival. This case report certainly represents a significant step for oncologists in understanding this disease.